Graphene oxide/hollow mesoporous silica composite for selective adsorption of methylene blue - Yilmaz, Muge Sari (ELSEVIER, 2022)
In this study, graphene oxide/hollow mesoporous silica composite was synthesized to apply selective adsorption of methylene blue from methyl orange and methylene blue mixture for the first time. In addition, layered double hydroxide/hollow mesoporous silica composite was also synthesized for comparison purpose. The effect of pH, contact time, and initial concentration on the adsorption were investigated. Changing the pH of the dye solution is effective in the adsorption behavior of the composite. The maximum adsorption capacities for the uptake of methyl orange at pH 3 and methylene blue at pH 9 from graphene oxide/hollow mesoporous silica were 270.27 and 476.19 mg g-1, respectively. On the other hand, this value for the uptake of methyl orange at pH 3 and methylene blue at pH 10 from layered double hydroxide/hollow mesoporous silica was found as 344.83 and 416.67 mg g-1, respectively. The kinetics and equilibrium data for adsorption of dyes using both composites fit the pseudo-second-order and Langmuir model, respectively. At pH 9, graphene oxide/hollow mesoporous silica showed remarkable selectivity for adsorption of methylene blue from the binary mixture, while at pH 10, layered double hydroxide/hollow mesoporous silica showed similar selectivity trend. The plausible adsorption mechanisms for methylene blue onto composite surfaces were examined Fourier transforms infrared, X-ray photoelectron spectroscopy, and scanning electron microscopy with energy dispersive X-ray spectroscopy. The electrostatic attraction and 7C-7C stacking interaction were the main adsorption mechanisms for the adsorption of methylene blue onto graphene oxide/hollow mesoporous silica. The regeneration experiments demonstrated the methylene blue adsorption/desorption efficiencies of graphene oxide/hollow mesoporous silica were more steady and higher than layered double hydroxide/hollow mesoporous silica.
Keywords: Selective adsorption; Graphene oxide; Layered double hydroxide; Hollow mesoporous silica; Composite; Adsorption mechanism; ANIONIC DYES; ORGANIC-DYES; REMOVAL; OXIDE; PERFORMANCE; ADSORBENTS; HYBRID; FUNCTIONALIZATION; NANOPARTICLES; DEGRADATION; Chemistry; Science & Technology - Other Topics; Materials Science